The challenge of ensuring gender equality in Vietnamese and English high schools: Espoused and real commitments. Issue 1 (13th March 2018) - Brundrett, Mark; Thuy Dung, Mai Thi
Abstract : Purpose: The purpose of this paper is to comparatively examine the issue of gender equality in high schools in Vietnam and England. Design/methodology/approach: Data gathering consisted of interviews with teachers in two high schools and the staff of a pedagogic university in Vietnam and staff of one high school and of the initial teacher training department of a university in England. Data were analysed using a combination of grounded theory, cross-cultural study and narrative analysis within a liberal feminist framework. Findings: The main findings from Vietnam include that despite a strong commitment to gender equality by the central government, both pedagogy and curriculum in Vietnamese high schools fail to promote gender equality, and that gender equality is, therefore, espoused rather than enacted. Findings from England revealed considerable success had been achieved in gaining equality of both opportunity and outcomes, but that a more sophisticated discourse on gender in education needed to emerge. Practical implications: Implications of the study include recommendations that more extensive training on gender equality is provided in both countries, but especially in Vietnam, in relation to curriculum, pedagogy and school leadership. Originality/value: This paper provides analysis and commentary on the issue of gender equality in both Vietnam and England. No such study has previously taken place in the context of Vietnam, and a comparison is offered with the more "developed" situation in the UK.